Unravelling the attributes of novel cyanobacteria Jacksonvillea sp. ISTCYN1 by draft genome sequencing. (October 2021) - Mishra, Arti; Gupta, Juhi; Kumari, Taruna; Pal, Ruchita; Thakur, I.S.
Graphical abstract: Highlights: First report of whole genome sequencing of genus Jacksonvillea sp. ISTCYN1 is reported. Desertifilum sp. IPPAS B-1220 was closest genus by phylogenetic tree constructed. Biofilm formation and biodegradation of polyethylene were shown by this strain. WGA revealed the presence of selenoproteins and gene involved in biotin synthesis. Gene prediction analysis showed presence of enzymes responsible for PE and PP degradation. Abstract: Filamentous cyanobacteria, Jacksonvillea sp. ISTCYN1 was isolated from agriculture field and cultured in BG-11 medium. This study, report the genome sequence of cyanobacteria Jacksonvillea that to the best of our knowledge is the first genome sequence of this genus. The 5.7 MB draft genome sequence of this cyanobacterium contains 5134 protein-coding genes. The phylogenetic tree was constructed based on genome and Desertifilum sp. IPPAS B-1220 validated the closest relationship with Jacksonvillea sp. ISTCYN1. The growth of strain ISTCYN1 has been reported in the presence of different types of plastic when used as a sole carbon source. SEM analysis revealed biofilm formation by cyanobacterial strain ISTCYN1 on the surface of high and low-density polyethylene and polypropylene. In the presence of these plastics, EPS production has also been reported by this strain. Whole genome sequence analysis reveals the presence of many genes involved in biofilm formation. The presence of key enzymes responsible for plastic degradation laccase, esterase, lipase, thioesterase, and peroxidase have been predicted in the genome analysis. Genome analysis also provides insight into the genes involved in biotin biosynthetic pathways. Furthermore, the presence of many selenoproteins reveals the selenium acquisition by this cyanobacterium.